Size Effect of Project Based Learning Model on Creative Thinking Skills of Civil Engineering Study Program Students - Alex Irawan Triyantho; Fantoni Fantoni; Tomi Apra Santosa (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effect size of the project-based learning model on the critical thinking skills of civil engineering study program students. This type of research is a meta-analysis. Data sources come from 9 national and international journals published from 2013-2023. Search for data sources through the google scholar database, ProQuest, Eric, and Plos ONE. Data collection techniques are direct observation and documentation. The data analysis technique is a quantitative analysis technique by calculating the effect size (ES) value and the average value (mean). These results explain the average value of Effect Size (ES = 0.970) and the mean value of 80.72. This finding shows that there is a significant effect of the project-based learning model on the creative thinking skills of civil engineering study program students compared to conventional learning models.